Correlation between Awareness of Blended Learning Techniques and Participation Rate in E-learning: a Case Study - Antoniadis, Nikolaos; Konetas, Dimitrios (International Journal of Advanced Corporate Learning (iJAC), 2011)
The use of information and communication technologies both in higher education and in business environments has been dramatically increasing in the past two decades. Blended learning (either synchronous or asynchronous) has been gaining ground and becoming a major alternative to standard teaching. In Greece, higher education institutions provide a substantial part of their curricula in electronic form and instructors are urged to use the e-learning tools more. However, students are not always willing to explore and take full advantage of the enhanced possibilities and often are not involved at all. Various modules of on-line education attract students in different ways, thus leading to a natural tendency to use different tools to fulfill their needs. This study aims at exploring the correlation between studentsâ?? awareness for this learning model, their level of participation in such learning formats and their final performance. Comparative results for participation and performance are presented for a variety of relevant interactive tools employed by the Learning Management System (LMS) of TEI of Epirus, a higher education institution in Greece.